Identification and confirmation of ethiological agents in selected high risk food from boarding school in Kuala Terengganu / Ahmad Fuad Omar - Omar, Ahmad Fuad (2019)
Salmonella sp, Escherichia coli, Bacillus cereus and Staphylococcus aureus are typical pathogenic foodborne bacteria causing food poisoning illness in humans. Mesophilic aerobes are an indicator of how susceptible the food can be at risk in being a mode of transmission for foodbome diseases. The objective of this study was to identify and confirm the ethiological agent contaminating selected high risk food from boarding schools in Kuala Terengganu. Based on previous data two of the most high risk food menu is egg sandwiches and chicken in spicy sauce. Each high risk food samples in this study were collected in duplicate from all thirteen different boarding school kitchens in Kuala Terengganu making a total (n=52). The results indicated the presence with mean of bacterial count in colony forming unit (CFU/g) of Salmonella with 3 x 10e2, Staphylococci 4.5 x 10e2, E. Coli 2.5 x 10 and Bacillus cereus 9.1 x 10e2, 1.4 x 10e2, 1.4 x 10e2. Salmonella and E. Coli both violates the Malaysia Food Act (MFA) 1985 and Australia Food Standard (AFS) 2001 which disclose that the permitted level not to be absent in 25g and 1 g of sample respectively while Staphylococci and Bacillus cereus are both within the permitted level of AFS 2001 which said should be <1 x 10e2. Results of mean bacterial count for Aerobic plate Count showed 5 out of 26 of samples violates MF A 1985 and 11 of them violates AFS2001 which stated should be below 1 x 10e5 and 1 x 10e4 respectively. Results of mean count for Coliforms showed 5 out of 26 of samples violates MF A 1985 and 6 of them violates AFS2001 which stated should be below 1 x 10e2 and 5 x 10e1 respectively. It was also found out that for both CSS and EGS there is a significant differences of microbial load in APC and coliform between SFP and SNFP with P-value of 0.001, 0.002 for CSS and 0.032, 0.025 for EGS with the sensitivity of P < 0.05.